Intravital Imaging Reveals Divergent Cytokine and Cellular Immune Responses to Candida albicans and Candida parapsilosis - Linda S. Archambault (American Society for Microbiology, 2019)
ABSTRACT Candida yeasts are common commensals that can cause mucosal disease and life-threatening systemic infections. While many of the components required for defense against Candida albicans infection are well established, questions remain about how various host cells at mucosal sites assess threats and coordinate defenses to prevent normally commensal organisms from becoming pathogenic. Using two Candida species, C. albicans and C. parapsilosis, which differ in their abilities to damage epithelial tissues, we used traditional methods (pathogen CFU, host survival, and host cytokine expression) combined with high-resolution intravital imaging of transparent zebrafish larvae to illuminate host-pathogen interactions at the cellular level in the complex environment of a mucosal infection. In zebrafish, C. albicans grows as both yeast and epithelium-damaging filaments, activates the NF-κB pathway, evokes proinflammatory cytokines, and causes the recruitment of phagocytic immune cells. On the other hand, C. parapsilosis remains in yeast morphology and elicits the recruitment of phagocytes without inducing inflammation. High-resolution mapping of phagocyte-Candida interactions at the infection site revealed that neutrophils and macrophages attack both Candida species, regardless of the cytokine environment. Time-lapse monitoring of single-cell gene expression in transgenic reporter zebrafish revealed a partitioning of the immune response during C. albicans infection: the transcription factor NF-κB is activated largely in cells of the swimbladder epithelium, while the proinflammatory cytokine tumor necrosis factor alpha (TNF-α) is expressed in motile cells, mainly macrophages. Our results point to different host strategies for combatting pathogenic Candida species and separate signaling roles for host cell types. IMPORTANCE In modern medicine, physicians are frequently forced to balance immune suppression against immune stimulation to treat patients such as those undergoing transplants and chemotherapy. More-targeted therapies designed to preserve immunity and prevent opportunistic fungal infection in these patients could be informed by an understanding of how fungi interact with professional and nonprofessional immune cells in mucosal candidiasis. In this study, we intravitally imaged these host-pathogen dynamics during Candida infection in a transparent vertebrate model host, the zebrafish. Single-cell imaging revealed an unexpected partitioning of the inflammatory response between phagocytes and epithelial cells. Surprisingly, we found that in vivo cytokine profiles more closely match in vitro responses of epithelial cells rather than phagocytes. Furthermore, we identified a disconnect between canonical inflammatory cytokine production and phagocyte recruitment to the site of infection, implicating noncytokine chemoattractants. Our study contributes to a new appreciation for the specialization and cross talk among cell types during mucosal infection.